Pemetaan Harmonisasi Kelembagaan untuk Penguatan Kelembagaan Pokdarwis Desa Sumberputih dalam Pengelolaan Hutan Pinus Semeru (HPS) - Solimun; Adji Achmad Rinaldo Fernandes; Riyanti Isaskar; Djoko Pramono (Jurnal Abdimas Pariwisata, 2025)
Mapping Institutional Harmonisation for Strengthening the Institutional Capacity of Pokdarwis in Sumberputih Village in the Management of Semeru Pine Forest (HPS) This study explores the potential and challenges of tourism management in Sumberputih Village, Malang Regency, with a focus on the Semeru Pine Forest. Despite having great tourism potential, current management is hampered by infrastructure problems and a lack of coordination between agencies. Using the Latent Dirichlet Allocation (LDA) method and K-Means Cluster Analysis, this study identified two main clusters: Cluster 1, characterised by moderate management and infrastructure conditions, and Cluster 2, which had better conditions. The analysis reveals that the cluster with better management (Cluster 2) achieves higher scores in organisational management, facilities and infrastructure, and community participation compared to Cluster 1. These findings underscore the need for institutional harmonisation and infrastructure improvement to increase the effectiveness of tourism management, as well as contribute to the development of sustainable tourism management models